SEMI EMPIRICAL BASED 3D-QSAR STUDIES OF SOME PHARMACOLOGICAL IMPORTANT COMPOUNDS - KISHOR ARORA, (International Journal of Pharma and Bio Sciences, 2013)
3D QSAR viz. 3 descriptor quantitative structure and activity relationship studies for a series of Schiff base derivatives of 2- Methyl pyridine -2- amine involving their semi-empirical quantum chemical descriptors and their laboratory reported activities against pathogens viz. E.coli and A.niger have been carried out and reported in the present communication. Graphs between observed and predicted activities, both in the terms of p(MIC) are also being reported on the basis of which this may be concluded that some parameters/descriptors have positive contribution towards the activity. The method has been proved to be useful for such type of studies.